Treatment of MRSA pneumonia: Clinical and economic comparison of linezolid vs. vancomycin – a retrospective analysis of medical charts and re-imbursement data of real-life patient populations - Wilke, Michael H.; Becker, Karsten; Kloss, Sebastian; Heimann, Sebastian M.; Goldmann, Anton; Weber, Bertram; Pletz, Mathias W.; Simon, Philipp; Petrik, Christian (GMS Infectious Diseases, 2017)
Objectives: To supplement the data collected in randomized clinical trials, the present study in patients with methicillin resistant (MRSA) pneumonia was conducted to explore the clinical effectiveness of linezolid and vancomycin in a routine clinical setting. Further, the overall costs of the patients' stay in the intensive care unit (ICU) were compared.Methods: This was a retrospective analysis of medical and reimbursement data of adult patients who were treated for MRSA pneumonia with linezolid or vancomycin. Since the subjects were not randomly assigned to treatments, propensity score adjustment was applied to reduce a potential selection bias.Results: In total, 226 patients were included; 95 received linezolid and 131 received vancomycin as initial therapy for MRSA pneumonia. Switches to another antibiotic were observed in 4 patients (4.2%) receiving linezolid and in 23 patients (17.6%) receiving vancomycin (logistic regression analysis; odds ratio linezolid/vancomycin: 0.183; 95% confidence interval [CI]: 0.052–0.647; p<0.01). All-cause in-hospital mortality was also lower in patients receiving linezolid (22 patients [23.2%] vs. 54 patients [41.2%]) (logistic regression analysis; odds ratio linezolid/vancomycin: 0.351; 95% CI: 0.184–0.671; p<0.01). The analysis of the total costs of stay in ICU did not reveal any major differences between the two treatment groups (cost ratio linezolid/vancomycin: 1.29; 95% CI: 0.84–1.98; p=0.24).Conclusions: These findings confirm in a routine clinical setting that linezolid is a valuable therapeutic alternative to vancomycin for the treatment of MRSA pneumonia. However, prospective studies in real-life patient populations are warranted.